Understanding Customer Perceptions of Real Estate Adverts: An Eye Tracking Study - Rohan Agarwal, Dr Preetha Menon (International Journal of Advanced Science and Technology, 2020)
Advertisements have an ability to mould the perceptions of the viewers and engage with them on a subconscious level to attract them to buy the product or service that the advertisement is about. Advertising is changing with the changing scenario especially with the advent of digital age; but advertising in real estate remains analogous to the older forms of advertising; banners, billboards, newspaper adverts, and pamphlets, along with some recently developed SMS marketing and the likes of social media marketing. Real estate buys are incredibly involved decisions and the impact or influence of advertisements on the intent to buy is of great interest. This study aims at finding the aspects of the advertisements that a viewer deems useful or informative enough to change their perception of the brand or the product/service that it is offering. Another area of interest for the study is to find the relation between the customer perception and the information displayed on the advertisement. Whether the fact that the advertisement is of a specific brand matters, or whether the branding has any effect on the perception of the information displayed on the advert is the intent of the study. The methodology that has been followed is that a series of print advertisements from the leading real estate developers in the print magazines and newspapers have been picked up and shown to the respondents in an eye tracking study. Their attention span and the elements of the advertisements that attract their attention have been recorded in a heat map, and the inferences about their perceptions about the advertisements have been developed further using a questionnaire that was put forth them right after the eye tracking exercise to prevent loss of information. What we found is that the brand name plays a vital role in the choice of customers for a real estate project. The customers are willing to pay a premium for a project by a brand that they know and trust, i.e., the developer with a high brand equity. What we also found is that advertisements need branding to attract the right customers, and minimalist advertisements do a great job in focusing the message that they want to communicate. Large and clear visuals and text also make a huge difference and attract the customer’s attention first, and most of the times retain it as well. Contact details aren’t termed as very important and can be kept away from the main areas of the advertising page and can be made smaller as an interested customer will search for the contact details on the page and contact the developer. Keywords: Eye-Tracking, real estate, brand awareness, brand recall, brand recognition, advertising, print media, brand image, brand equity.